ChemInform Abstract: Unnatural Chiral N‐tert‐Butanesulfinyl α‐Amino Acid Synthesis: A General Synthetic Strategy to N‐Boc‐Phenylalanine Analogue Alternatives. Issue 7 (22nd February 2013) - Lin, Li; Fu, Xu; Ma, Xiaojuan; Zhang, Jinlong; Wang, Rui
Abstract The asymmetric addition of organozinc reagents to the chiral imino acetate (II) proceeds with high diastereoselectivity.